PENINGKATAN KUALITAS HIDUP MASYARAKAT KAWASAN PESISIR MELALUI PENATAAN PERMUKIMAN KAMPUNG NELAYAN - Prajnawrdhi, T.A.; Paramadhyaksa, I.N.W.; Aritama, A.A.N.; Mahastuti, N.M.M.; Satria, M.W.; Alvina, J.; Aryawan, B.L.; Wiraputra, I.G.G.S.A. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p01, 2024)
Sangsit Village, which is one of the villages on the north coast of Bali, is one of the villages that has a fishing village. The current condition of the fishing village can still be said to be a village that has inadequate facilities and infrastructure and the condition of some residents' houses is still below standard. Considering that the location of this village is quite strategic and is included in the tourist area, this fishing village has great potential to be revitalized to become better and utilize its potential as part of a coastal tourist area. This article presents a concept for structuring a fishing village that can accommodate the commercial and business activities of the population to improve the standard of living of the population. Qualitative methods involving field observations and interviews were used to produce structuring concepts. The results show that an integrated environmental planning design that can accommodate commercial activities can provide opportunities for the community to improve the economy, and is also accompanied by the provision of UMKM zones. Improvements to utilities, landscaping, and environmental management also support the quality of life of the Sangsit Village fishing village community. Carrying out integrated physical planning of fishing villages is also accompanied by education about the importance of the environment and healthy homes in improving the quality of life of fishing village communities so that it can improve the standard of living and quality of life of fishing village communities as a whole. Keywords: area, community, fishermen, coast, arrangement, quality, settlements, Sangsi